PROS and CONS in general medicine and geriatrics, 2020 - Cucinotta, Domenico (Acta Biomedica Atenei Parmensis, 2021)
In 2020 many researches were published concening non Covid pathologies. In the field of general medicine and geriatrics a look is given to oxygen therapeutic use, soft surgical treatments of benign prostatic hyperplasia, nonalcoholic steatohepatitis treatment, use of SGLT2 inhibitors in cardiac failure and a proposal for treatment of severe claudicatio intermittens.